2022
DOI: 10.1186/s12864-022-08524-6
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression analysis of resistant and susceptible rice cultivars to sheath blight after inoculation with Rhizoctonia solani

Abstract: Background Rice sheath blight, caused by Rhizoctonia solani Kühn (teleomorph: Thanatephorus cucumeris), is one of the most severe diseases in rice (Oryza sativa L.) worldwide. Studies on resistance genes and resistance mechanisms of rice sheath blight have mainly focused on indica rice. Rice sheath blight is a growing threat to rice production with the increasing planting area of japonica rice in Northeast China, and it is therefore essential to explore the mechanism of sheath blight resistance… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 118 publications
0
13
1
Order By: Relevance
“…The fact that there were more DEGs in GD66 than that in Lemont at both 24 and 48 hpi indicated that the resistant genotype GD66 recruited more genes than the susceptible genotype Lemont in fighting against the pathogen. Our results are different from some previous reports that more DEGs were found in sheath blight–susceptible cultivars than that in sheath blight–resistant cultivars ( Zhang et al., 2017 ; Shi et al., 2020 ; Yang et al., 2022 ). It means that the GD66 may have different mechanism than other resistant cultivars during rice– R. solani interaction.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The fact that there were more DEGs in GD66 than that in Lemont at both 24 and 48 hpi indicated that the resistant genotype GD66 recruited more genes than the susceptible genotype Lemont in fighting against the pathogen. Our results are different from some previous reports that more DEGs were found in sheath blight–susceptible cultivars than that in sheath blight–resistant cultivars ( Zhang et al., 2017 ; Shi et al., 2020 ; Yang et al., 2022 ). It means that the GD66 may have different mechanism than other resistant cultivars during rice– R. solani interaction.…”
Section: Discussioncontrasting
confidence: 99%
“…The transcriptome profiles between the susceptible cultivar Lemont and the moderately resistant cultivar Teqing in response to sheath blight disease were studied, and it showed that regulation of photosynthesis, photorespiration, jasmonic acid, and phenylpropanoid pathways contribute to rice resistance to R. solani ( Shu et al., 2019 ). Transcriptome analysis showed that the defense system in resistant rice cultivars involved the expression of PR genes, key transcription factors, PAL genes, and the enrichment of defense-related pathways ( Yang et al., 2022 ). Comparative transcriptome analysis suggested that photosynthesis, photorespiration, and jasmonic acid and phenylpropanoid metabolism played important roles in disease resistance ( Zhang et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The promoter analysis of these target genes helped to understand that the up-regulated genes were controlled by other WRKY proteins and the down-regulated genes were regulated by MYB and AP2/EREBP proteins (Qiu et al ., 2009). WRKY TF family are important regulators in defence response pathways against pathogen infection (Yang et al ., 2022). However, the promoter analysis in the entire genome will help to identify the possible target genes in the entire rice genome controlled by WRKY13 TF.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, AG1-IA primarily infects rice plants, AG2 infects cruciferous vegetables, and AG3 prefers solanaceous plants under natural conditions ( Hane et al., 2014 ). Rice SBD caused by AG1-IA and potato black scurf disease caused by AG3 have been widely investigated because of their economic and ecological importance in agriculture ( Zrenner et al., 2020 ; Yang et al., 2022 ). However, relatively few studies have examined the relationship between R. solani AG3 and other economically important crops, including tobacco.…”
Section: Introductionmentioning
confidence: 99%